Fostering school connectedness online for students with diverse learning needs: inclusive education in Australia during the COVID-19 pandemic. Issue 1 (1st January 2021) - Page, Angela; Charteris, Jennifer; Anderson, Joanna; Boyle, Christopher
ABSTRACT: Over the first few months of 2020, the schooling sector shifted to distance education as governments moved to bring the virus, COVID-19, under control. Education sectors rapidly developed online environments. In this milieu teachers have made swift changes to accommodate their students' diverse range of learning needs. In this article, we draw on a qualitative study in Australia to identify key challenges and approaches for fostering school connectedness when students with special educational needs are suddenly required to be educated at distance. A heuristic to define school connectedness is supported that involves connecting with supportive adults; a sense of belonging; positive peer relationships; engagement with learning, and the experience of a positive online climate. Findings from this case study signal that, despite the efforts of educators, students who have special educational needs can slip between the cracks and are at great risk of losing connection both academically and emotionally. There were challenges with students who did not engage in online learning at all. Although practitioners in the study worked with parents to provide the structures for curricula to be addressed, teachers working at distance could enhance school connectedness through fostering teacher and student, and student and student relationships.